Zebrafish: An Attractive Model to Study Staphylococcus aureus Infection and Its Use as a Drug Discovery Tool - Sari Rasheed; Franziska Fries; Rolf Müller; Jennifer Herrmann (MDPI AG, 2021)
Non-mammalian in vivo disease models are particularly popular in early drug discovery. Zebrafish (Danio rerio) is an attractive vertebrate model, the success of which is driven by several advantages, such as the optical transparency of larvae, the small and completely sequenced genome, the small size of embryos and larvae enabling high-throughput screening, and low costs. In this review, we highlight zebrafish models of Staphyloccoccus aureus infection, which are used in drug discovery and for studying disease pathogenesis and virulence. Further, these infection models are discussed in the context of other relevant zebrafish models for pharmacological and toxicological studies as part of early drug profiling. In addition, we examine key differences to commonly applied models of S. aureus infection based on invertebrate organisms, and we compare their frequency of use in academic research covering the period of January 2011 to January 2021.